2014
DOI: 10.1136/bjophthalmol-2014-305451
|View full text |Cite
|
Sign up to set email alerts
|

The risk of acute coronary syndrome after retinal artery occlusion: a population-based cohort study

Abstract: We found that RAO increased the risk for ACS. We recommend thorough follow-up cardiovascular examinations and medical prevention for ACS in patients following RAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
2
52
0
2
Order By: Relevance
“…Furthermore, several studies have reported that the incidence of stroke and acute coronary syndrome is significantly high following RAO events. 8,39 This suggests that ESRD patients with hypertension should be considered for cardiovascular monitoring to ameliorate RAO and prevent stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have reported that the incidence of stroke and acute coronary syndrome is significantly high following RAO events. 8,39 This suggests that ESRD patients with hypertension should be considered for cardiovascular monitoring to ameliorate RAO and prevent stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies show that RAO is a predictor of ACS, stroke, and mortality [1,2,7]. Chang et al showed a 70% increase in the risk of ACS in patients with RAO, and even higher in patients with central retinal artery occlusion (CRAO) [1]. In 2012, the same authors reported that RAO increased the risk of stroke by a factor of 2.07, and the risk was increased more than threefold in patients below 60 years of age [2].…”
Section: Discussionmentioning
confidence: 86%
“…Risk factors for RAO include hypercholesterolemia, hypertension, carotid artery and aortic arch atherosclerosis, ischemic heart disease, kidney dysfunction, diabetes, stroke, smoking, mitral and aortic valve disease, and thrombi or vegetations which might be a source of embolic material [8,10]. Multiple studies show that RAO is a predictor of ACS, stroke, and mortality [1,2,7]. Chang et al showed a 70% increase in the risk of ACS in patients with RAO, and even higher in patients with central retinal artery occlusion (CRAO) [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies using the same database have been published. 32,33 Thus, selection bias in referral centers and chances of misdiagnosis may be reduced. The NHI Research Database contains all claims data, thereby ensuring accuracy and avoiding recall bias because data are recorded electronically.…”
Section: Discussionmentioning
confidence: 99%